Implementation of Guidance and Counseling Teacher Competencies in the Actuating of Guidance and Counseling in Schools - Aqra, Naila Rumaisha; AS, Uman Suherman (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
Guidance and counseling teachers have a crucial role in helping students overcome various personal, social, and academic problems and optimally develop their potential. By having appropriate competencies, guidance, and counseling teachers can provide services that are more effective and relevant to student needs, thereby improving overall student welfare and achievement. This article aims to determine the implementation of guidance and counseling in schools according to teacher competency. The method used in writing this article is using the literature review method. The literature review was used to collect information regarding the competency of guidance and counseling teachers and the implementation of guidance and counseling in schools. Implementation of guidance and counseling teacher competencies has enormous benefits in the educational context. Competent guidance and counseling teachers can provide quality guidance and counseling services to students, helping them overcome problems, understand themselves, and develop their potential optimally. Apart from that, implementing guidance and counseling teacher competencies can also improve the overall quality of education, improve relationships between students and teachers, and provide support for students with special needs.